2016
DOI: 10.1108/info-12-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

How important is mobile telephony for economic growth? Evidence from MENA countries

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…In our selected research, the link between MFS and economic growth is discussed in relation with the increasing coverage of financial services (Kpodar & Andrianaivo ). For instance, Ghosh () empirically examined the impact of financial inclusion on economic development by analysing data from the Middle East and North African countries. The study demonstrated that a 1% increase in the portion of the population who use mobile devices improves household income by roughly 0.3% points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our selected research, the link between MFS and economic growth is discussed in relation with the increasing coverage of financial services (Kpodar & Andrianaivo ). For instance, Ghosh () empirically examined the impact of financial inclusion on economic development by analysing data from the Middle East and North African countries. The study demonstrated that a 1% increase in the portion of the population who use mobile devices improves household income by roughly 0.3% points.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a similar 1% increase in financial inclusion has doubled the impact on household income. Based on this analysis, Ghosh () concluded that financial inclusion actually contributes to economic development in developing countries. Kikulwe, Fischer, and Qaim () also empirically showed that smallholder farmers who use MFS in the rural areas of Kenya tend to have higher profits than those who do not use the services.…”
Section: Resultsmentioning
confidence: 99%
“…Work on Africa that uses the UNDP's measure of IHDI supports these arguments (Asongu, 2013; Asongu et al ., 2016). Mobile and fixed line penetration also contribute positively to growth in Middle East and North African countries (Sassi and Goaied, 2013; Ghosh, 2016).…”
Section: Mobile Technology and Developmentmentioning
confidence: 99%
“…These improvements in making the unbanked population a part of the formal financial system by improving their access to financial services can serve as a poverty eradication tool, foster inclusive growth and help countries meet the Millennium Development Goals (Chibba, 2009). Ghosh (2016) finds that mobile telephony in India has had a positive and significant impact on growth, financial inclusion and loan disbursement.…”
Section: Mobile Banking and Financial Inclusion: Transforming Economiesmentioning
confidence: 99%
“…The mobile banking platform, which comprises mobile or m-wallets and over-the-counter (OTC) transactions, has grown rapidly around the world and has the potential to reduce barriers to financial inclusion and thus transform economies (Klein & Mayer, 2011). The benefits are even more pronounced for economies with a weak financial architecture and where formal banking entails considerable costs in terms of time and distance (Ghosh, 2016).…”
Section: Introductionmentioning
confidence: 99%